Network(ed) TV: Collaboration and Intervention at Fernsehgalerie Gerry Schum and Videogalerie Schum. - Farrell, Robyn (Afterimage)
The article focuses on the contribution of documentary filmmaker Gerry Schum, the conceptual gallery Fernsehgalerie Gerry Schum and commercial gallery Videogalerie Schum to television and video art productions between 1968 and 1973. Several artists including Jan Dibbets, Robert Smithson and Gino de Dominicis collaborated with Schum in television broadcasts and exhibitions titled "Land Art" and "Identifications." Schum's mastery of interventionist broadcasting is mentioned.